TEACHING WRITING FOR STUDENTS OF SMK WIRAHUSADA MEDAN - Elovani Mulinta Sinuraya; Berlin Sibarani; Morada Tetty (REGISTER: Journal of English Language Teaching of FBS-Unimed, 2020)
This study aims at describing how the teacher teaches the students to write texts to the eleven grade students of SMK Wirahusada Medan and the underlying reasons of why  the teacher did the way she did. Qualitative research design was used by the researcher to conduct this study. The subject of this study was English teacher who taught the eleven grade students of SMK Wirahusada Medan in academic year 2018/2019. The data were collected by observing, video or audio recording, and interview. The data were analysed by using Miles and Huberman data analysis techique. The findings of the study showed that most of the ways of teaching were focusing on telling the students the genre knowledge of text than focusing on teaching writing. The underlying reasons of the teacher’s ways in teaching writing were due to (1) Teacher believed that by reminding the definition of the text made the students be able to differentiate the text. (2) the teacher believed that by knowing the purpose of material, the students are able to differ a text with other text, (3) the teacher believed that the the generic structure and language feature helped the students to know the steps of writing text, (4) teacher believed that by giving the task from the easiest types, the students will slowly were able to write their other texts later.Keywords:Teaching, Teaching writing, Qualitative research